Optimization of alkaline protease production from Halotolerant bacillus subtilis and its application in Tannery effluent treatment - R. AJI,; R. RAJA JEYASEKAR, (International Journal of Pharma and Bio Sciences, 2018)
Alkaline protease producing Bacillus subtilis strain AJ was isolated from the saltern pond at South West Coast of India. The process parameters were optimized to enhance the production of alkaline protease. The nutritional factors such as, carbon, nitrogen and ions, and also physical factors such as, NaCl, pH and temperature were optimized for the maximum yield of alkaline protease. Enzyme production was maximum in the culture medium containing 4% NaCl and over a broad pH range (pH 6.0 to 9.0). The tested protease activity showed a linear increase with increase in medium temperature up to 35 ºC and at higher temperatures, the enzyme production declined. In B. subtilis strain AJ, supplementation of glucose, sucrose, fructose, trehalose and starch significantly enhanced more amount of enzyme production than that of control. Among the tested nitrogen sources, yeast extract showed maximum amount of protease activity. The ions, Mn2+, Na2HPO4 and Ca2+also enhanced enzyme production. In the present study, the chromium level of control tannery wastewater was 1712 mg/l. However the biological treatment reduced chromium level after 24h (43±2.6%) and 48 h (71 ± 4.8%) of treatment with the bacterium, B. subtilis strain AJ. This chromium reduction was mainly due to the metabolic activity of the selected B. subtilis strain AJ.